Organic compost in promoting growth and photosynthetic performance of Pereskia aculeata Mill. (Cactaceae) saplings - Nina Machado Suzigan; Gustavo dos Santos Cardoso; Nicole Almeida Barbosa; Giulianna Carolina Pincela da Costa; Geovana Gomes; Sara Dias Moura; Mônica Ellen Regis de Oliveira; Luiz Fernandes Cardoso Campos; Hyrandir Cabral de Melo; Letícia de Almeida Gonçalves (Ciência Rural)
ABSTRACT: Pereskia aculeata, commonly known as ora-pro-nóbis, is a Non-Conventional Food Plant (NCFP) native to Brazil. Considering the limited number of studies on species propagation and the importance of more sustainable practices for small-scale farmers, the objective was to evaluate the growth of P. aculeata saplings cultivated in substrates with different proportions of organic compost. The saplings were obtained by cuttings and cultivated in four distinct substrates, comprising three treatments and one control group. The substrates were prepared from a mixture of ant mound soil and commercial substrate, with the treatments determined by the amount of organic compost added. In the control group, no organic compost was incorporated, while in the other treatments, the compost represented 25, 50, and 75% of the total substrate mass. Mixed linear models were applied to morphological and physiological variables. It was possible to observe that, the higher the amount of organic compost in the substrate, the greater the growth of the shoots that developed from the cuttings, a result reflected primarily in the increased length and number of leaves on the largest branch, and the dry mass of the above-ground part. The rate of net photosynthesis and effective quantum efficiency of Photosystem II also significantly increased with the incorporation of organic compost into the substrate. It can be concluded that the addition of organic compost promoted the growth of P. aculeata cutting saplings, as well as their photosynthetic performance.